2017
DOI: 10.1103/physrevd.96.035007
|View full text |Cite
|
Sign up to set email alerts
|

Resonant di-Higgs boson production in the bb¯WW channel: Probing the electroweak phase transition at the LHC

Abstract: We analyze the prospects for resonant di-Higgs production searches at the LHC in the bbW þ W − (W þ → l þ ν l , W − → l −ν l ) channel, as a probe of the nature of the electroweak phase transition in Higgs portal extensions of the Standard Model. In order to maximize the sensitivity in this final state, we develop a new algorithm for the reconstruction of the bbW þ W − invariant mass in the presence of neutrinos from the W decays, building from a technique developed for the reconstruction of resonances decayin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 72 publications
2
93
0
1
Order By: Relevance
“…• As mentioned in the Introduction, resonant di-Higgs production at the LHC [11,14,29,38] and a future 100 TeV hadron collider [12,13,15,39] would be expected to probe portions of the parameter space with m 2 > 2m 1 . Ref.…”
Section: Current Constraints and Projected Sensitivitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…• As mentioned in the Introduction, resonant di-Higgs production at the LHC [11,14,29,38] and a future 100 TeV hadron collider [12,13,15,39] would be expected to probe portions of the parameter space with m 2 > 2m 1 . Ref.…”
Section: Current Constraints and Projected Sensitivitiesmentioning
confidence: 99%
“…A particularly powerful probe will be measurements of the Zh production cross-section at lepton colliders, which can deviate from its SM predicted value due to mixing effects and the wavefunction renormalization of the Higgs-like scalar h [18,19]. A combination of these approaches, in addition to gravitational wave experiments such as LISA [20], show promise in probing the EWPT in singlet models [10][11][12][13][14][15][16][17][20][21][22][23][24][25][26].…”
Section: Jhep08(2017)096 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibilities for a SFOEWPT with an additional real singlet scalar (dubbed the "xSM" [17]), along with its phenomenological consequences for collider studies, have been studied extensively [18][19][20][21][22][23][24][25][26][27][28][29]. The xSM implies the existence of two neutral mass eigenstates, H 1;2 , that are mixtures of the neutral doublet and real singlet.…”
Section: Introductionmentioning
confidence: 99%
“…3(c). If a new scalar is sufficiently heavy and can decay on-shell into two SM-like Higgs bosons, it has been shown that the new scalar might significantly enhance the di-Higgs production rate over the SM prediction via its resonant production by gluon-gluon fusion [21][22][23][24][25][26][29][30][31][32][33]. Using the narrow width approximation, the resonant production cross section can be approximately written as…”
Section: +0004mentioning
confidence: 99%